Estudo da ação antinociceptiva e antiinflamátoria do 1-Nitro-2-Feniletano, principal constituinte da Aniba Canelilla - LIMA, Anderson Bentes de (2008)
Aniba canellila is a large size tree found in Northern region of Brazil and largely used in folk medicine. The infusate of its leaves and bark skin is believed to be a good antispasmodic, antidiarreic, anti-inflammatory, tonic agent and a good stimulant of digestive and the central nervous systems. This study was designed to evaluate the effects 1-nitro-2-phenylethane, main component of Aniba canelilla. We evaluated the antinociceptive and anti-inflammatory effects of the 1-nitro-2-phenylethane which is the main component of essential oil of Aniba canelilla. For nociception models were designed the writhing test, hot plate test and formalin test. For inflammation models were designed the croton oil-induced ear edema, rat paw edema induced by carrageenan and dextran, and leucocyte and neutrophil migration on carrageenan-induced peritonitis. In the writhing test, the 1-nitro-2-phenylethane dosed at 15, 25 and 50 mg/kg reduced the abdominal writhes in a significant manner. In the hot plate test (55 ? 0.5? C), the 1-nitro-2-phenylethane dosed at 50, 100 and 200 mg/kg did not induced alterations in the latency time when compared to the control. In the formalin test, the 1-nitro-2-phenylethane dosed at 50 and 25 mg/kg reduced in a significant manner the second phase of the algic stimulous. In addition, its antinociception was reversed by naloxone in the second phase. The 1-nitro2-phenyletahne produced inhibition of rat paw edema induced by carrageenan and dextran in a dose-dependent manner at the doses of 25 and 50 mg/kg. Doses of 25 and 50 mg/kg caused a dose-dependent inhibition of croton oil-induced ear edema in mice (with inhibition of 73% and 79%, respectively). Pretreatment (60 min) of rats with 1-nitro-2-phenylethane (25 mg/kg) significantly decreased leucocyte and neutrophil migration on carrageenan-induced peritonitis (with inhibition of 22,55% and 38,13%, respectively). Our results suggest that 1-nitro-2-phenylethane has analgesic activity which, according to the tests employed, is probably of peripheral origin. The mechanism involved is not completely understood, however these results suggest that opiod receptors are involved in the antinociceptive action of the 1-nitro-2-phenylethane. Further, our results suggest that 1-nitro-2-phenylethane has anti-inflammatory activity which, according to the tests employed, is probably of peripheral origin.